“Redupnya” Pesan dan “Menguatnya” Informasi: Refleksi Komunikasi Sebagai Sistem Seleksi - Sholikhah, Nur Imroatus (Retorik: Jurnal Ilmu Humaniora, 2025)
The rapid development of digital technology has fundamentally transformed the landscape of contemporary communication studies. Information now circulates in large volumes, spread rapidly, and is often no longer structured within complete, coherent messages. This paper proposes the need for reflection through two questions: (1) How the possibility of communication can be constructed through frameworks beyond the logic of message transmission; and (2) to what extent communication studies that emphasize information can contribute to reducing the complexity of social problems in modern society. This reflection revisits the evolution of communication studies by challenging three influential theoretical perspectives: Harold Lasswell, Jürgen Habermas, and Niklas Luhmann. The Lasswellian model is challenged especially in the context of message confusion and unclear authority of the message sender. Habermas’ communicative rationality is confronted by the dominance of algorithmic logic and emotional expressions that permeate social media spaces. Meanwhile, Luhmann’s systems theory raises further questions regarding the relevance of communication studies in the digital era, where information circulates autonomously, often without requiring the active involvement of human actors. Within the information society, communication is no longer solely a bridge between subjects but also operates as a selection system. Communication processes occur autonomously through the selection of meaning within the social system and decoupled from the ‘burden’ of individual consciousness. This approach to communication as a selection system is particularly relevant for positioning the role of information within the increasingly disruptive digital landscape. Amidst the information flood and a growing crisis of meaning, communication studies need to move beyond the traditional paradigm towards more contextualized and systemic frameworks.